Mobility in the Bakken: rhetorical place-making in contested Native and white rural space - Miller, Henry D., author; Dickinson, Greg, advisor; Vasby Anderson, Karrin, committee member; Schneider, Lindsey, committee member (Colorado State University. Libraries, 2020)
This thesis engages the intricacies of oil extraction in and around the Bakken region through confronting rhetorical modes by which settler colonialism is practiced and resisted in a modern context. Today, oil boomtowns rhetorically transform a modern-day frontier and reestablish a colonial order that justifies resource extraction and alters spatial relations on the North Dakota landscape. Using in-situ rhetorical criticism, I methodologically weave myself into the texts as both a critic and participant in how space is produced. This thesis consists of an introduction, two main analytical chapters, and a conclusion. In the first analytical chapter, I argue Watford City produces spaces and narratives of whiteness that normalize settler colonialism and situate white bodies as natural occupants of oil boom space. Serving as a metaphor for whiteness, oil fracturing or "fracking" functions as a rhetorical design of both city and museum. In the next analytical chapter, I explore the complexity of overlapping white and Native spaces on the tribal municipalities of New Town and Four Bears Village. To rhetorically comprehend the oil boom spatially on the Fort Berthold Reservation, it is necessary to understand how place is constructed through the production of archived memories and survivance. By situating both Native and white space next one another, this thesis argues that oil boom spaces in North Dakota are being (re)occupied by predominantly white male bodies that hinder the livability of Native bodies in Native spaces. All the while, the Fort Berthold Reservation resists settler colonial practices through everyday acts that decolonize space and place through archived memory and survivance.
Keywords: North Dakota; settler colonialism; survivance; rhetorical fracking; archived memory; space and place